Prevalence of gastrointestinal zoonotic helminths in dogs of Kathmandu, Nepal - Satyal, RC; Manandhar, S; Dhakal, S; Mahato, BR; Chaulagain, S; Ghimire, L; Pandeya, YR (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Considering the close association of dog and human beings and increasing trend of pet rearing, it is important to know the status of zoonotic helminths of pet and stray dogs and awareness of owners about this in Kathmandu, Nepal. This study was carried out to determine the prevalence of gastrointestinal zoonotic helminth parasites in dogs and to assess the awareness about canine helminth zoonoses in pet owners. MATERIALS AND METHODS: This cross-sectional study was conducted from September- 2012 to December- 2013. A total of 210 fecal samples (105 each from pet and stray dogs) were collected perrectally and examined by using Formalin-Ether Concentration method. Questionnaire survey was carried out among dog owners. RESULTS: The prevalence of gastrointestinal helminths was 46.7% (98/210). Out of 98 positive samples five different parasite species observed were Ancylostoma spp. 52.0% (51/98), Toxocara canis 41.8% (41/98), Taenia/Echinococcus spp. 15/98 (15.3%), Dipylidium caninum, 9.2% (9/98), and Trichuris vulpis, 5.1% (5/98). Prevalence was higher in stray dogs (56.2% vs. 37.1%) (p<0.05); in females (51.6% vs. 39.8%) (p>0.05); in younger dogs up to 2 years of age (56.3% vs. 35.7%) (p<0.05); in non-dewormed dogs (72.7% vs. 33.0%) (p<0.05) and in dogs sharing rooms with owner (46.1% vs. 13.8%) (p<0.05). Only 11.4% of the owners surveyed were aware about canine helminth zoonoses. CONCLUSIONS: Due to potential risk of zoonotic helminths to human beings and low level of zoonoses awareness in pet owners, there is need of generating awareness to pet owners regarding periodic anthelminthic treatment of pet dogs and other prevention and control measures. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8211 Int J Infect Microbiol 2013;2(3):91-94